Video assisted thoracoscopic management of primary spontaneous pneumothorax - Farhan Ahmed Majeed; Yasser Saeed Khan; Ahmed Raza; Tashfeen Imtiaz; Usama Zafar; Adeel Wyne (Journal of the Pakistan Medical Association, 2020)
Objective: To analyze the outcome of Video assisted Thoracoscopy (Vats) in Primary Spontaneous Pneumothorax (PSP). Methods: This case series was carried out from Jan 2010 to Jan 2017 in Dept of Thoracic Surgery CMH Rawalpindi and Lahore. A total of 98 patients underwent Video-assisted thoracoscopic for PSP. Inclusion criteria were physiologically fit patients with PSP for recurrent attacks, occupational hazards and prolonged air leak. Exclusion criteria included secondary spontaneous pneumothorax, previous pleurodesis and physiologically unfit patient for general anesthesia. Vanderschueren's thoracoscopic classification was used for macroscopic staging. A 3-port technique was used for apical stapling with partial pleurectomy up to 6th rib. Parietal pleura and diaphragm was also abraded. Results: Occupational hazard was the commonest indication for surgery, n= 39 (39.7%). This was followed by recurrent pneumothorax n=37 (37.7%), persistent air leak n= 19 (19.38%), and contra lateral pneumothorax n=4 (4.08). Mean age was 22.8 years ± 6.5. Majority of the cases were in stage 3 of Vanderschueren’s classification, n=69 (70.4%). Stage 4 were n= 18 and stage 2 were n=7. Mean operative time was 51minutes ±14.4. Postoperative prolonged air leak occurred in 3 patients and post-operative neuralgia occurred in 8 patients. Mean follow-up was 22 months ± 5.5, range 5-24 months for all patients. One had generalized recurrence and 2 patients have subpulmonic trapping of air. Conclusions: Video-assisted thoracoscopic stapling and pleurectomy is an effective definitive treatment for primary spontaneous pneumothorax when indicated with minimal recurrence. Keywords: Video-assisted thoracoscopy, blebs, pneumothorax. Continuous...